Analisis Efektivitas Pengelolaan Aset Kemitraan di Divisi Sarana dan Prasarana Perum Perhutani Divre Jawa Timur - Adib Fatihunniam; Dhani Ichsanuddin Nur (Universitas Muhammadiyah Surabaya, 2025)
This analysis aims to evaluate the effectiveness of partnership asset management within Perum Perhutani Divre East Java using the Plan–Do–Check–Act (PDCA) framework. Public asset management plays a strategic role in enhancing operational efficiency and generating economic value, yet its implementation still faces challenges related to data accuracy, asset conditions, marketing limitations, and regulatory rigidity. The findings indicate that the optimization process begins with identifying and verifying underutilized assets, followed by offering them to potential partners and preparing cooperation agreements grounded in accountability and transparency. Monthly evaluations are conducted to monitor revenue realization, asset utilization, and partner compliance, although effectiveness remains constrained by informal marketing practices, variations in asset potential, and misalignment between revenue targets and actual field conditions. Through PDCA implementation, improvement efforts focus on strengthening asset information systems, enhancing cross-unit coordination, modernizing asset marketing strategies, and revising regulations to be more adaptive to partner needs. This analysis emphasizes that transparent governance, adequate human resource capacity, and continuous evaluation are essential elements in achieving productive and sustainable partnership asset management